Contribution of the Mutis Timau Protected Forest to Community Income in the Forest Management Unit of South Central Timor Regency, Timor Island, Indonesia - Fransiskus Xaverius Dako; Ris Hadi Purwanto; Lies Rahayu Wijayanti Faida; Sumardi (Jurnal Manajemen Hutan Tropika, 2020)
Communities in and around the forest always interact and use the resources to satisfy their daily needs for survival. Forest resources obtained by the community are used to satisfy family needs, and one is an additional family income. This study aimed at determining the contribution of Mutis Timau protected forest to community income. In order to knowing the income that the community earns from the forest, a survey was conducted in nine villages located in and around Mutis Timau protected forest that started from January to June 2018. Nine villages were purposively selected that Mutis Timau protected forest area is administratively under those villages whose communities directly interact with the protected forest. The technique of collecting data was a questionnaire with 353 respondents selected proportionally in each village. Also, observation and literature study were adopted. The data were descriptively analyzed. The results denote that Mutis Timau protected forest provide income to the community through non-timber forest products of IDR1,637,510,566 year-1 of the total income of IDR45,260,686,262 year-1. Community income earned from Mutis Timau protected forest is very low (3.62%) compared to the income gained from horticultural food crops (66.29%) and livestock (30.09%). The income is directly earned from the sale of non-timber forest products to the consumers without having product processes in particular for hunting wild animals, fungus, tubers, and honey. Honey delivers higher income besides other non-timber forest products, such as hunting wild animals, fungus, and tubers.